Effectiveness of Community Pharmacy Diabetes and Hypertension Care Program: An Unexplored Opportunity for Community Pharmacists in Pakistan - Malik, Madeeha; Hussain, Azhar; Aslam, Usman; Hashmi, Ayisha; Vaismoradi, Mojtaba; Hayat, Khezar; Jamshed, Shazia (Frontiers in Pharmacology, 2022)
Background: Effective management of diabetes mellitus and hypertension depends on the efficacy of therapy and patient adherence to medication therapy followed by the execution of non-pharmacological approaches such as patient counseling. Community pharmacists can effectively contribute to patient care as they have the expertise and accessibility to do the task appropriately. The objective of the study was to evaluate the impact of pharmacist counseling on blood pressure and glucose control among hypertensive and diabetic patients attending community pharmacies in Pakistan. Method: A randomized, controlled, single-blinded, pre-post-intervention study design was used. The respondents included patients diagnosed with diabetes mellitus (Type I or II) and hypertension visiting community pharmacies to purchase their regular medicine. A simple random sampling technique by lottery method was used to select community pharmacies in groups A (intervention, n=4) and group B (control n=4). The total number of patients was 40 in each group while estimating a drop-out rate of 25%. Patients in the intervention group received special counseling. Blood pressure and blood glucose were checked after every 15 days for six months. Pre-validated tools such as hypertension knowledge level scale, diabetes knowledge questionnaire 24, and brief medication questionnaire were used. Data were coded and analyzed using SPSS 21. Wilcoxon test (p<0.05) was used to compare pre-post intervention knowledge regarding the disease, while the Mann-Whitney test (p<0.05) was used to find differences in medication adherence among control and intervention groups. Results: A significant improvement in mean knowledge scores of patients with diabetes (12.72±3.47 vs 19.97±2.66) and hypertension (14.32±2.42 vs 18.35±2.31) in the intervention group receiving counseling for six months than control group (p<0.05) was noted. Furthermore, the fasting blood glucose levels (8.95±1.45) and systolic BP (127.63±6.88) were significantly controlled after six months in the intervention group. Conclusion: The current study results concluded that community pharmacists' counselling has a positive impact on blood glucose and blood pressure management among diabetic and hypertensive patients.